Light scattering models of white blood cells and back-scattering distribution analysis of them - Wang, Ya-Wei; Bu, Min; Shang, Xue-Fu; Yue, Qu-Wei (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
Focusing on the light scattering technique and its application in cell identification, the analysis of the morphological structures of the WBCs (white blood cells) has been made, and the light scattering models of five types of the WBCs have been built. Based on the light scattering theory and applying numerical simulation techniques to a systematic study of the back-scattering intensity distribution of five types of the WBCs, some significant effects made by the internal and external morphological structures of the WBCs and the changes of their refractive index to their back-scattering distribution and certain relations between them have been found. Thus, the back-scattering theory and its application have been expanded, and it is very useful to improve the technique of cell identification.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 527-539
Keywords: optyka; cell identification; WBC (leukocyte); analysis of scattering; back-scattering